Rapid asphalt net crack repairing agent and preparation method thereof
By using SBS modified emulsified asphalt, SBR latex, cationic aqueous polyurethane and other components in asphalt pavement mesh crack repair agent, and adding polyurethane/chlorhexidine acetate to modify montmorillonite nano-SiO2 functionalized basalt fibers, the problems of short pavement service life and complex repair process after repair in the prior art are solved, rapid curing and efficient repair are achieved, extending the service life of the repair layer and reducing costs.
Patent Information
- Application Number
- CN202411866939.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-19
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When dealing with the problem of cracking asphalt pavement, the service life of the pavement after repair is short and the repair process is complicated, which increases maintenance costs.
A rapid asphalt mesh crack repair agent is used, including SBS modified emulsified bitumen, SBR latex, cationic aqueous polyurethane, HPMC cellulose, dispersant polyvinyl alcohol, fillers and polyurethane/chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fibers, to achieve rapid curing and efficient repair through specific formulation design and construction processes.
The repair agent cures in a short time, improving the adhesion between the repair agent and the original asphalt surface, enhancing the weather resistance and anti-aging properties of the repair layer, extending the service life of the repair layer, optimizing the construction performance, and reducing material usage and cost.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of asphalt, and in particular relates to a rapid asphalt crack repairing agent and a preparation method thereof. Background Art
[0002] Asphalt pavement is one of the most widely used advanced pavement types in road engineering. Its characteristic is that it is paved by mixing asphalt materials with mineral materials. This mixture not only improves the durability of the pavement material, enabling it to withstand the impact of vehicle driving and natural disasters, but also after construction and paving, the asphalt pavement shows the characteristics of flatness, waterproofness and long-term durability.
[0003] Although asphalt pavement is popular for its durability and easy maintenance, it is also facing problems such as cracks and potholes as the weight of vehicles and traffic volume increase. These damages, combined with rain erosion and the continuous action of heavy vehicles, can cause structural damage to asphalt pavement. In order to extend the service life of asphalt pavement, cracks or potholes should be repaired as soon as they are found to prevent further damage from affecting traffic.
[0004] At present, highway and municipal departments in many regions are facing some challenges in dealing with the cracking problem. They often ignore the early stages of cracking and fail to take timely repair measures. Over time, the cracking problem will gradually worsen, resulting in the need to use pothole repair technology to deal with local cracking, while for large areas of cracking, more complex repair methods such as milling and cold regeneration may be required. These methods not only affect the performance of the pavement, but also increase the subsequent maintenance costs. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a rapid asphalt crack repair agent and a preparation method thereof.
[0006] The present invention is achieved through the following technical scheme: a rapid asphalt crack repair agent, which includes, by mass: 100 parts of SBS modified emulsified asphalt; 2-5 parts of SBR latex; 3-8 parts of cationic water-based polyurethane; 0.2-0.6 parts of HPMC cellulose; 0.5-1 parts of dispersant polyvinyl alcohol; 10-30 parts of filler; 0.3-2 parts of polyurethane / chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber; and 0.05 parts of catalyst diamine ether solution.
[0007] The polyurethane / chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber of the invention is polyurethane-chlorhexidine acetate modified montmorillonite / nano-SiO2.
[0008] SBR latex is a stable emulsion formed by low-temperature polymerization of butadiene and styrene, which can enhance the low-temperature performance of the crack repair agent and enhance its durability and wear resistance. The one-component water-based polyurethane can increase the elasticity of the repair agent and play a shock-absorbing effect.
[0009] Furthermore, the composition comprises, by mass: 100 parts of SBS modified emulsified asphalt; 3 parts of SBR latex; 5 parts of cationic waterborne polyurethane; 0.5 parts of HPMC cellulose; 0.8 parts of dispersant polyvinyl alcohol; 20 parts of filler; 1 part of polyurethane / chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber; and 0.05 parts of catalyst diamine ether solution.
[0010] Furthermore, the catalyst bisamine ether solution is a 70% bis(dimethylaminoethyl) ether solution, which is composed of 70% by mass of bis(dimethylaminoethyl) ether and 30% by mass of dipropylene glycol.
[0011] Furthermore, it also includes basalt fiber; the length of the basalt fiber is 3-6mm; the surface density is 200±20g / m 2 .
[0012] Furthermore, the filler is selected from one or more of talc, diatomaceous earth and kaolin.
[0013] Furthermore, the preparation method of the polyurethane / chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber is: Firstly, nano-SiO2 and polyurethane-chlorhexidine acetate modified montmorillonite were pretreated and placed in a vacuum of 0.1MPa at 60°C overnight; the pretreated nano-SiO2 and polyurethane-chlorhexidine acetate modified montmorillonite were mixed in a mass ratio of 1:1 and added into epoxy resin bisphenol A E51 to obtain a mixed solution; the mixed solution was ultrasonicated for 0.5h and then placed in a vacuum environment of 0.1MPa to remove the gas in the mixed solution; wherein the mass ratio of the total mass of nano-SiO2 and polyurethane-chlorhexidine acetate modified montmorillonite to the epoxy resin bisphenol A E51 was 1:1.
[0014] Furthermore, the mass ratio of the mixture of nano-SiO2 and polyurethane-chlorhexidine acetate modified montmorillonite is 1:1~5.
[0015] Furthermore, the mass ratio of the mixture of nano-SiO2 and polyurethane-chlorhexidine acetate modified montmorillonite is 1:3.
[0016] Furthermore, the preparation method of the polyurethane-chlorhexidine acetate modified montmorillonite is: 6 g of chlorhexidine acetate was dissolved in 100 mL of deionized water, and then 100 mL of a 20 g / L aqueous solution of montmorillonite was added, and the obtained mixed solution was refluxed at 80° C. for 3 h, and then filtered to obtain a precipitate, and the precipitate was washed with pure water until no chloride ions were present in the washing solution, and the washed precipitate was vacuum dried for 24 h to obtain chlorhexidine acetate modified montmorillonite; The polyurethane was heated at 80°C for 24h under a 0.1M vacuum environment, and then the chlorhexidine acetate-modified montmorillonite and the polyurethane were mixed in a mass ratio of 1:0.2, heated to 150°C, and stirred at 70rpm for 10min to obtain polyurethane-chlorhexidine acetate-modified montmorillonite.
[0017] The present invention also provides a method for preparing a rapid asphalt crack repair agent, which is characterized in that it comprises the following steps: heating SBS modified emulsified asphalt, SBR latex, cationic water-based polyurethane, HPMC cellulose, and dispersant polyvinyl alcohol to 50°C, adding filler, maintaining the temperature at 50°C and stirring for 0.5h, adding polyurethane-chlorhexidine acetate modified montmorillonite nano-SiO2 and catalyst diamine ether solution, stirring at 50°C for 0.5h, and obtaining a rapid asphalt crack repair agent.
[0018] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The patching agent can be cured in a short time through a specific formula design, thus realizing the rapid repair of asphalt cracks. The combined use of SBS modified emulsified asphalt and cationic waterborne polyurethane improves the adhesion of the patching agent to the original asphalt surface, ensuring that the patch layer is closely integrated with the original road surface. By adding SBR latex and polyurethane / chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber, the weather resistance and anti-aging properties of the patching agent are enhanced, and the service life of the patch layer is extended. By controlling the type and proportion of fillers and the use of catalyst diamine ether solution, the construction performance of the patching agent is optimized, making it easy to apply and spread.
[0019] 2. This application uses polyurethane / chlorhexidine acetate to modify montmorillonite nano-SiO2 functionalized basalt fibers, which increases the mechanical strength of asphalt pavement repair and improves the effect after repair. In addition, the preparation is simple, the repair method is also simple and convenient, and no additional large equipment is required. By optimizing the formula and construction process, the material consumption and construction cost are reduced, and the economy of the repair agent is improved. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0021] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
[0022] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to those of ordinary skill in the art that these specific details do not have to be employed to practice the present invention. In other embodiments, in order to avoid confusing the present invention, known structures, materials or methods are not specifically described. The materials, instruments and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. The technical means used in the examples, unless otherwise specified, are conventional means well known to those skilled in the art.
[0023] In the prior art, the patching agent used to repair the cracked asphalt pavement mainly includes components such as asphalt, latex and filler. Among them, the specific type and amount of asphalt determine the needle penetration and ductility of the patching agent. Although the existing patching agent can repair the cracked asphalt pavement, the repaired asphalt pavement with network cracks has almost no obvious cracks, and the water permeability coefficient of the pavement is greatly reduced, with a good repair effect. However, the service life of the repaired asphalt pavement is short. The reason is that the tensile strength and impact strength of the patching agent are low.
[0024] Therefore, in order to increase the service life of the repaired asphalt pavement, the present invention improves the existing repair agent and improves the service life of the repaired asphalt pavement by improving the tensile strength and impact strength of the repair agent.
[0025] The polyetheramine curing agent in the present invention is BASF EC301; the basalt fiber is purchased from a commercial product, with a length of 3-6 mm; a thickness of 0.18 mm, and a surface density of 200±20 g / m 2 ; SBR latex was purchased from Shandong Qiaolong Environmental Protection Technology Co., Ltd., and SBS modified emulsified asphalt was purchased from Daozhijian (Shanghai) New Materials Co., Ltd. Cationic waterborne polyurethane AH-1730 was purchased from Anhui Dawei Huatai New Materials Technology Co., Ltd.; polyvinyl alcohol can be purchased from products produced by Ningxia Dadi Recycling Development Co., Ltd. The remaining reagents were also purchased from commercially available products.
[0026] Embodiment 1: A rapid asphalt crack repair agent comprises, by mass, 100 parts of SBS modified emulsified asphalt; 3 parts of SBR latex; 5 parts of cationic waterborne polyurethane; 0.5 parts of HPMC cellulose; 0.8 parts of dispersant polyvinyl alcohol; 20 parts of filler talcum powder; 1 part of polyurethane / chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber; and 0.05 parts of catalyst diamine ether solution.
[0027] The bisamine ether solution is a 70% bis(dimethylaminoethyl) ether solution, which is composed of 70% by mass of bis(dimethylaminoethyl) ether and 30% by mass of dipropylene glycol (DPG).
[0028] Among them, polyurethane-chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber can be abbreviated as polyurethane-chlorhexidine acetate modified montmorillonite nano-SiO2. Specifically, the role of polyurethane-chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber is equivalent to basalt fiber, and its role in the repair agent is to improve the mechanical strength of the repair agent. In the process of preparing polyurethane-chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber, basalt fiber is not used, and "functionalized basalt fiber" can be understood as its functional equivalent to basalt fiber. It is well known that adding fibers to the repair agent can improve the tensile strength and crack resistance of the repair area, which is particularly suitable for sections that need to withstand large loads or frequent temperature changes. However, through experiments, it was found that although adding fibers to the repair agent can improve the tensile strength and crack resistance of the repair area to a certain extent, the improvement is limited, and it still cannot solve the problem of the service life of the asphalt pavement after repair. Therefore, the present invention designs polyurethane-chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber which can replace basalt fiber in function.
[0029] SBS modified emulsified asphalt, SBR latex, cationic water-based polyurethane, HPMC cellulose, and dispersant polyvinyl alcohol are heated to 50°C, and then fillers are added. The temperature is maintained at 50°C and stirred for 0.5 h. Polyurethane / chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber and catalyst diamine ether solution are then added, and stirred at 50°C for 0.5 h to obtain a rapid asphalt crack repair agent.
[0030] The preparation method of polyurethane / chlorhexidine acetate modified montmorillonite / nano-SiO2 functionalized basalt fiber (polyurethane / chlorhexidine acetate modified montmorillonite-nano-SiO2) is as follows: Firstly, nano-SiO2 and polyurethane-chlorhexidine acetate modified montmorillonite were pretreated and placed in a vacuum of 0.1MPa at 60°C overnight; the pretreated nano-SiO2 and polyurethane-chlorhexidine acetate modified montmorillonite were mixed in a mass ratio of 1:1 and added into epoxy resin bisphenol A E51 to obtain a mixed solution; the mixed solution was ultrasonicated for 0.5h and then placed in a vacuum environment of 0.1Mpa to remove the gas in the mixed solution; polyetheramine (BASF EC301) was added for curing, wherein the polyetheramine was 30% of the weight of the epoxy resin bisphenol; wherein the mass ratio of the total mass of nano-SiO2 and polyurethane-chlorhexidine acetate modified montmorillonite to the epoxy resin bisphenol A E51 was 1:1;.
[0031] The preparation method of polyurethane-chlorhexidine acetate modified montmorillonite is: Take 6g of chlorhexidine acetate and dissolve it in 100mL of deionized water, then add 100mL of 20g / L montmorillonite aqueous solution, then reflux heat the obtained mixed solution at 80°C for 3h, then filter to obtain a precipitate, wash the precipitate with pure water until there is no chloride ion in the washing liquid, and vacuum dry the washed precipitate for 24h to obtain chlorhexidine acetate modified montmorillonite.
[0032] The polyurethane was heated at 80°C for 24h under a 0.1M vacuum environment, and then the chlorhexidine acetate-modified montmorillonite and the polyurethane were mixed in a mass ratio of 1:0.2, heated to 150°C, and stirred at 70rpm for 10min to obtain polyurethane-chlorhexidine acetate-modified montmorillonite.
[0033] Embodiment 2: The difference between this embodiment and embodiment 1 is that the mass ratio of nano-SiO2 to polyurethane-chlorhexidine acetate modified montmorillonite in the polyurethane-chlorhexidine acetate modified montmorillonite / nano-SiO2 functionalized basalt fiber is 1:2.
[0034] Embodiment 3: The difference between this embodiment and embodiment 1 is that the mass ratio of nano-SiO2 to polyurethane-chlorhexidine acetate modified montmorillonite in the polyurethane-chlorhexidine acetate modified montmorillonite / nano-SiO2 functionalized basalt fiber is 1:3.
[0035] Embodiment 4: The difference between this embodiment and embodiment 1 is that the mass ratio of nano-SiO2 to polyurethane-chlorhexidine acetate modified montmorillonite in the polyurethane-chlorhexidine acetate modified montmorillonite / nano-SiO2 functionalized basalt fiber is 1:4.
[0036] Embodiment 5: The difference between this embodiment and embodiment 1 is that the mass ratio of nano-SiO2 to polyurethane-chlorhexidine acetate modified montmorillonite in the polyurethane-chlorhexidine acetate modified montmorillonite / nano-SiO2 functionalized basalt fiber is 1:5.
[0037] Embodiment 6: This embodiment is based on the embodiment 1, and the difference from the embodiment 1 is that: one portion of basalt fiber is added to the formula of the embodiment 1; the length of the basalt fiber is 3-6 mm; the surface density is 200±20 g / m 2 .
[0038] Comparative Example 1: The difference from Example 1 is that montmorillonite / nano-SiO2 functionalized basalt fiber is used instead of polyurethane / chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber.
[0039] The preparation method of montmorillonite / nano-SiO2 functionalized basalt fiber is as follows: Firstly, nano-SiO2 and montmorillonite are pretreated and placed in a vacuum of 0.1MPa at 60°C overnight; the pretreated nano-SiO2 and montmorillonite are mixed in a mass ratio of 1:1 and added into epoxy resin bisphenol A E51 to obtain a mixed solution; the mixed solution is ultrasonicated for 0.5h and placed in a vacuum environment of 0.1MPa to remove the gas in the mixed solution; polyetheramine (BASF EC301) is added for curing, wherein the polyetheramine is 30% of the weight of the epoxy resin bisphenol; wherein the mass ratio of the total mass of nano-SiO2 and montmorillonite in epoxy resin bisphenol A E51 is 1:1.
[0040] Comparative Example 2: The difference from Example 1 is that chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber is used instead of polyurethane / chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber.
[0041] The preparation method of chlorhexidine acetate modified montmorillonite / nano-SiO2 functionalized basalt fiber is as follows: Firstly, nano-SiO2 and chlorhexidine acetate modified montmorillonite were pretreated and placed in a vacuum of 0.1MPa at 60°C overnight; the pretreated nano-SiO2 and chlorhexidine acetate modified montmorillonite were mixed in a mass ratio of 1:1 and added into epoxy resin bisphenol A E51 to obtain a mixed solution; the mixed solution was ultrasonicated for 0.5h and then placed in a vacuum environment of 0.1MPa to remove the gas in the mixed solution; polyetheramine (BASF EC301) was added for curing, wherein the polyetheramine was 30% of the weight of the epoxy resin bisphenol; wherein the mass ratio of the total mass of nano-SiO2 and chlorhexidine acetate modified montmorillonite to the epoxy resin bisphenol A E51 was 1:1.
[0042] The preparation method of chlorhexidine acetate modified montmorillonite is: Take 6g of chlorhexidine acetate and dissolve it in 100mL of deionized water, then add 100mL of 20g / L montmorillonite aqueous solution, then reflux heat the obtained mixed solution at 80°C for 3h, then filter to obtain a precipitate, wash the precipitate with pure water until there is no chloride ion in the washing liquid, and vacuum dry the washed precipitate for 24h to obtain chlorhexidine acetate modified montmorillonite.
[0043] Comparative Example 3: The difference from Example 1 is that polyurethane-modified montmorillonite is used instead of polyurethane / chlorhexidine acetate-modified montmorillonite nano-SiO2 functionalized basalt fiber.
[0044] The preparation method of polyurethane modified montmorillonite is as follows: The polyurethane was heated at 80°C for 24 h under a 0.1 M vacuum environment, and then montmorillonite and polyurethane were mixed in a mass ratio of 1:0.2, heated to 150°C, and stirred at 70 rpm for 10 min to obtain polyurethane-modified montmorillonite.
[0045] Comparative Example 4: This comparative example is based on Example 1, and the difference from Example 1 is that the polyurethane-chlorhexidine acetate modified montmorillonite nano-SiO2 in Example 1 is replaced by basalt fiber.
[0046] A rapid asphalt crack repair agent comprises, by mass, 100 parts of SBS modified emulsified asphalt; 3 parts of SBR latex; 5 parts of cationic waterborne polyurethane; 0.5 parts of HPMC cellulose; 0.8 parts of dispersant polyvinyl alcohol; 20 parts of filler talc powder; 1 part of basalt fiber; and 0.05 parts of catalyst diamine ether solution.
[0047] Test Example 1: The tensile strength was measured with reference to GB / T 1040.3-2006 “Determination of tensile properties of plastics”, with a tensile speed of 2 mm / min. Three specimens were taken from each group for testing, and the results were averaged.
[0048] The impact strength was measured with reference to GB / T 1843-2008 “Determination of cantilever beam impact strength of plastics”. Three specimens were taken from each group for testing and the results were averaged.
[0049] Hamburger rutting test: The rutting plate is formed according to the initial strength molding method, and the Hamburger rutting test is carried out after demoulding and curing. The test index is the number of load actions when the rutting depth reaches 20mm, which is used to evaluate the life of the asphalt pavement repair material.
[0050] Table 1 Performance test Referring to Table 1, it can be seen from Examples 1 to 6 that, relative to Comparative Examples 1 and 2, in the prior art, referring to Comparative Example 1, montmorillonite / nano-SiO2 functionalized basalt fiber is used to enhance the mechanical strength of the repair agent. By using chlorhexidine acetate to modify montmorillonite, the tensile strength and Hamburger rutting test are slightly improved compared to the prior art, but the impact strength is reduced. By further using chlorhexidine acetate to modify montmorillonite and polyurethane in combination, the tensile strength, impact strength, and Hamburger rutting test are significantly improved, with unexpected technical effects.
[0051] Since the asphalt in the asphalt crack repair agent in each embodiment of the present invention and the comparative example is SBS modified emulsified asphalt, the needle penetration of the asphalt crack repair agent in each embodiment and the comparative example is similar. When measured at a temperature of 25°C using a standard injection for 5 seconds, the needle penetration of the asphalt crack repair agent in each embodiment and the comparative example is between 60-65dmm. The elongation length of the asphalt crack repair agent when it is broken is measured using an ductility meter, and the elongation of the asphalt crack repair agent in each embodiment and the comparative example is between 70-80mm. That is, there is no great difference in the needle penetration and elongation of the asphalt crack repair agent in each embodiment of the present invention and the comparative example. Moreover, for asphalt pavements with severe local cracks, the asphalt pavements repaired with the asphalt crack repair agents prepared in each embodiment of the present invention and the comparative example have almost no obvious cracks, and the water permeability coefficient of the asphalt pavement is greatly reduced, achieving a very ideal repair effect for asphalt pavements with large-area cracks.
[0052] The inventive point of the present invention is not to improve the needle penetration and ductility of the repair agent, nor to improve the combination effect of the repair agent and the cracked asphalt pavement, but to improve how to improve the mechanical strength and impact resistance of the asphalt cracked repair agent, so as to improve the performance of the asphalt cracked repair agent, and further increase the service life of the asphalt pavement repaired with the asphalt cracked repair agent.
[0053] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A fast asphalt crack repair agent, characterized in that: The composition comprises, by mass: 100 parts of SBS modified emulsified asphalt; 2 to 5 parts of SBR latex; 3 to 8 parts of cationic waterborne polyurethane; 0.2 to 0.6 parts of HPMC cellulose; 0.5 to 1 parts of dispersant polyvinyl alcohol; 10 to 30 parts of filler; 0.3 to 2 parts of polyurethane / chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber; and 0.05 parts of catalyst diamine ether solution.
2. According to the rapid asphalt crack repair agent described in claim 1, it is characterized in that: The composition includes, by mass: 100 parts of SBS modified emulsified asphalt; 3 parts of SBR latex; 5 parts of cationic waterborne polyurethane; 0.5 parts of HPMC cellulose; 0.8 parts of dispersant polyvinyl alcohol; 20 parts of filler; 1 part of polyurethane / chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber; and 0.05 parts of catalyst diamine ether solution.
3. According to the rapid asphalt crack repair agent described in claim 1, it is characterized in that: The catalyst bisamine ether solution is a 70% bis(dimethylaminoethyl) ether solution, which is composed of 70% by mass of bis(dimethylaminoethyl) ether and 30% by mass of dipropylene glycol.
4. A rapid asphalt crack repair agent according to claim 1, characterized in that: Also includes basalt fiber; the length of the basalt fiber is 3-6mm, and the surface density is 200±20g / m 2 .
5. A rapid asphalt crack repair agent according to any one of claims 1 to 2, characterized in that: The filler is selected from one or more of talc, diatomaceous earth and kaolin.
6. A rapid asphalt crack repair agent according to claim 1, characterized in that: The preparation method of the polyurethane / chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber is as follows: Firstly, nano-SiO2 and polyurethane-chlorhexidine acetate modified montmorillonite were pretreated and placed in a vacuum of 0.1MPa at 60°C overnight; the pretreated nano-SiO2 and polyurethane-chlorhexidine acetate modified montmorillonite were mixed in a mass ratio of 1:1 and added into epoxy resin bisphenol A E51 to obtain a mixed solution; the mixed solution was ultrasonicated for 0.5h and then placed in a vacuum environment of 0.1MPa to remove the gas in the mixed solution; wherein the mass ratio of the total mass of nano-SiO2 and polyurethane-chlorhexidine acetate modified montmorillonite to the epoxy resin bisphenol A E51 was 1:
1.
7. A rapid asphalt crack repair agent according to claim 6, characterized in that: The mass ratio of nano-SiO2 and polyurethane chlorhexidine acetate modified montmorillonite is 1:1~5.
8. A rapid asphalt crack repair agent according to claim 6, characterized in that: The mass ratio of nano-SiO2 and polyurethane chlorhexidine acetate modified montmorillonite is 1:
3.
9. The rapid asphalt crack repair agent according to any one of claims 6 to 8, characterized in that: The preparation method of the polyurethane chlorhexidine acetate modified montmorillonite is as follows: 6 g of chlorhexidine acetate is dissolved in 100 mL of deionized water, 100 mL of a 20 g / L montmorillonite aqueous solution is added, the obtained mixed solution is reflux-heated at 80° C. for 3 h, precipitates are obtained by filtration, the precipitates are washed with pure water until no chloride ions exist in the washing solution, and the washed precipitates are vacuum-dried for 24 h to obtain the chlorhexidine acetate modified montmorillonite; polyurethane is heated at 80° C. for 24 h under a 0.1 M vacuum environment, the chlorhexidine acetate modified montmorillonite and polyurethane are mixed at a mass ratio of 1:0.2, the mixture is heated to 150° C., and the mixture is stirred at 70 rpm for 10 min to obtain the polyurethane-chlorhexidine acetate modified montmorillonite.
10. The method for preparing the rapid asphalt crack repair agent according to claim 1, characterized in that: The following steps are involved: SBS modified emulsified asphalt, SBR latex, cationic water-based polyurethane, HPMC cellulose, and dispersant polyvinyl alcohol are heated to 50°C, and then fillers are added. The temperature is maintained at 50°C and stirred for 0.5 h. Polyurethane / chlorhexidine acetate modified montmorillonite nano-SiO2 functionalized basalt fiber and catalyst diamine ether solution are then added, and stirred at 50°C for 0.5 h to obtain a rapid asphalt crack repair agent.
Citation Information
Patent Citations
Waterproof asphalt composition
CN109666305A
Normal-temperature asphalt mixture and preparation method
CN110713362A
Polyurethane-modified asphalt-based non-cured waterproof coating, and preparation method and application thereof
CN111518476A
Rapid repairing material for net-shaped crack defects and preparation process of material
CN111519489A
Self-heating warm mix asphalt repair material and construction method thereof
CN111892336A